The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15196881
|View full text |Cite
|
Sign up to set email alerts
|

Diatomaceous Earth—Lightweight Pozzolanic Admixtures for Repair Mortars—Complex Chemical and Physical Assessment

Abstract: The presented research is focused on the complex assessment of three different types of diatomaceous earth and evaluation of their ability for application as pozzolana active admixtures applicable in the concrete industry and the production of repair mortars applicable for historical masonry. The comprehensive experimental campaign comprised chemical, mineralogical, microstructural, and physical testing of raw materials, followed by the analyses and characterization of pozzolanic activity, rheology and heat ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…The excess amount of C-S-H can replace the pore holes in the concrete mix and refine and densify the interfacial transition zone (ITZ) between aggregate particles and cement paste [53]. The immediate filler effect of DE was also reported by [52]. Moreover, a similar kind of split tensile strength increment at an early-age strength increment was recorded by [54].…”
Section: Split Tensile Strengthmentioning
confidence: 83%
See 2 more Smart Citations
“…The excess amount of C-S-H can replace the pore holes in the concrete mix and refine and densify the interfacial transition zone (ITZ) between aggregate particles and cement paste [53]. The immediate filler effect of DE was also reported by [52]. Moreover, a similar kind of split tensile strength increment at an early-age strength increment was recorded by [54].…”
Section: Split Tensile Strengthmentioning
confidence: 83%
“…Beyond 15%, there is a decrease in compressive strength that may be caused by an inadequate amount of calcium hydroxide (C-H) in blended cement, which would be needed to react with much more silica following DE addition [51]. It was also reported that mechanical parameters could be improved by up to 15% substitute for Portland cement [52]. The design shows that partially replacing cement with DE by up to 20% enhanced the compressive strength compared to the control mix.…”
Section: Compressive Strength Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In their extensive scientific review, Becerra-Duitama and Rojas-Avellaneda [ 16 ] highlight, along with other materials, the positive influence of diatomites on the cement-pozzolan interface, mainly in mechanical properties, durability, water absorption, and permeability. Pavlíková et al [ 17 ] have focused their research on the improvement of mortars with diatomites intended for the repair and restoration of historic buildings and monuments and found that the optimal ratio of Portland cement to diatomite is 10%. Ince et al [ 18 ] have monitored the mechanical properties of cement mortars previously reinforced with cellulose fibers, which have been introduced into the mixtures as a substitute for fine aggregate, resulting in a significant increase in mechanical compressive strength and an evident physical and chemical stability of the specimens.…”
Section: Introductionmentioning
confidence: 99%
“…To promote cement soil strength stability and alleviate environmental pollution, natural materials can be used to modify cement soil. Studies have found that diatomite can improve the mechanical properties of cement-based materials [ 12 , 13 , 14 ]. Diatomite is a biosilicite formed by ancient unicellular diatoms through long-term geological processes.…”
Section: Introductionmentioning
confidence: 99%